SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON KARYAWAN BARU MENGGUNAKAN METODE ADDITIVE RATIO ASSESSMENT (ARAS) (STUDI KASUS : PT. MEDIA FORUM NUSANTARA) - Aldi Pranaja Hidayatullah; Latipah Latipah (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Employees are one of the supporting factors for a company, because by having qualified employees, in accordance with the qualifications, and criteria needed by the company, then the company can develop and move forward in the future. No exception PT. Media Forum Nusantara is currently in need of new employees who are suitable to work in the company. But PT. Media Forum Nusantara is faced with a problem where there are many prospective employees who take the selection test, it will cause the number of incoming files to be adjusted to the criteria owned by the company and requires a lot of time. Making it prone to file errors. To minimize the occurrence of errors and the length of time used, a Decision Support System was made to determine the best prospective employees who will work in the company. Decision Support System method used is Additive Ratio Asssessment (ARAS)